La Fonte Ardennaise et ses marchés - Prati, Bruno (Presses universitaires de Franche-Comté, 2024)
The story of La Fonte Ardennaise is that of the transformation of a small artisan foundry founded in the 1920s by a moulder in an area that had always specialised in cast iron work, into a company of European stature at the beginning of the 21st century. The company's growth was based on the effective market adaptation strategies of entrepreneurs who were unfamiliar with the mental models of established foundrymen. It is also the story of a family that has managed to combine entrepreneurial dynamism and family adventure at every stage of the company's growth. This is undoubtedly the key to the success and longevity of this large family SME.